Analysis of Relations Between Aboveground Biomass and Vegetation Indices Derived from Sentinel-2 Satellite Data - Altanchimeg, Tsolmon; Damdinsuren, Amarsaikhan; Tseveen, Batchuluun; Batdorj, Byambadolgor (Journal of Institute of Mathematics and Digital Technology, 2022)
The aim of this research is to study the relationship between the estimated aboveground forest biomass and spectral vegetation indices derived from the visible and infrared bands of multispectral Sentinel-2 satellite data. The study area is situated in Teshig soum of Bulgan aimag, the northern part of Mongolia and geographically it belongs to a forest-steppe natural zone. To calculate the aboveground biomass in sampling plots, forest stand parameters such as diameter at breast height (DBH) and tree height (H) have been measured, and allometric equations were used. In the final analysis, we investigated the relationship between the aboveground biomass measured at sampling plots and several predefined vegetation indices. The relationships between the aboveground biomass values and vegetation indices were explored by the use of a linear regression model. Of the outputs, the best results demonstrating the highest level of significance were obtained by the uses of the LAI (with R2=0.61) and SR (with R2=0.59). Газрын Дээд Биомасс болон Sentinel-2 Дагуулын Мэдээнээс Тооцсон Ургамлын Индекс Хоорондын Хамаарлын Шинжилгээ Хураангуй: Судалгааны ажлын зорилго нь олон бүсчлэлийн Sentinel-2 дагуулын үзэгдэх гэрлийн болон ойрын нэл улаан туяаны мужийн сувгуудыг ашиглан тооцоолсон ургамлын индекс, газрын дээд биомасс хоорондын хамаарлыг судлахад оршино. Судалгааны талбай болох Булган аймгийн Тэшиг сум нь Монгол орны хойд хэсэгт орших бөгөөд байгалийн бүс бүслүүрийн хувьд ойт хээрийн бүсэд хамаарна. Газрын дээд биомассыг тооцоолохдоо дээж талбайгаас цээжний өндрийн диаметр (DBH) болон модны өндөр (H) зэрэг параметрүүдийг хэмжиж, аллометрийн тэгшитгэлийг ашигласан бөгөөд дээж талбай дээр хэмжсэн газрын дээд биомасс болон ургамлын индексүүдийн хоорондын хамаарлыг шугаман регрессийн загвар ашиглан шинжил- сэн болно. Судалгаанаас гарсан үр дүнгүүдээс өндөр ач холбогдолтой индексүүд нь ургамлын навчны талбайн индекс LAI (R2=0.61), ойрын нэл улаан туяаны болон улаан гэрлийн сувгуудын харьцаа SR (R2=0.59) байв. Түлхүүр үгс: Монгол, зайнаас тандах судлал, аллометрийн тэгшитгэл, регрессийн загвар